China a personal encounter with the People's Republic - Romualdez, Daniel; Romualdez, Philip (Englewood Cliffs, N.J. Prentice Hall, 1977)
Text and color photographs present aspects of contemporary life in the People's Republic of China.
Keywords: Romualdez, Daniel; China -- Description and travel